Potential for Development of Seaweed Cultivation Business Post Covid-19 Post in the Marine Area, Serangan City, Denpasar - Bali - Gede Agus Pratama; Sang Ayu Made Putri Suryani; I Nengah Muliarta (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research was to outline the possibilities for seaweed farming in Serangan Denpasar, Bali's maritime waters. study based on Aqua Modis satellite photography findings. The results of satellite photography for water depth are used, together with SST (Sea Surface Temperature) distribution photos taken between January and June 2019 and January and June 2023. Based on observations, the attack sea's waters contain an area of 70.61 Ha that could be used for seaweed production in 2019. 71.82 Ha could be used for seaweed farming in 2023